Penggunaan Model Pembelajaran Kooperatif Learning Jenis Think PairShare dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Bahasa Arab di Pesantren Paqusatta - Iin Suriya Ningsih; Mahfud Iffendi; Anggra Prima (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to examine the implementation of the cooperative learning model Think Pair Share (TPS) in improving students’ learning outcomes in Arabic language learning at Pesantren Paqusatta, as well as to identify the supporting and inhibiting factors in its application. This research employs a qualitative descriptive method and is categorized as field research. Data were collected through observation, interviews, and document studies using a descriptive technique. The findings reveal that the implementation of the Think Pair Share model in Arabic language learning is effective in enhancing students’ learning outcomes and engagement. Students became more active and confident through the three main stages of the Think Pair Share model: first, providing a question or problem for students to think about individually (think); second, asking them to discuss in pairs (pair) to share answers and refine their understanding; and third, selecting several pairs to present their discussion results in front of the class (share), followed by correction and feedback. The supporting factors include providing opportunities for students to think independently, encouraging peer discussion, presenting ideas in front of the class, fostering collaboration among students, accelerating comprehension of learning materials, and helping improve Arabic speaking skills. Meanwhile, the inhibiting factors consist of limited vocabulary, difficulties in constructing sentences, students’ shyness or lack of confidence and fear of making mistakes when speaking, the need for more time in discussion and presentation, and limited facilities.